Gambaran Penerapan Health Belief Model Pada Balita Stunting Di Wilayah Puskesmas Minggir Sleman - Nendhi Wahyunia Utami; Melisa Putri Rahmadhena (Stikes Muhammadiyah Klaten, 2020)
The Health Belive Model (HBM) is a model of individual health beliefs in determining the attitude of doing or not doing health behavior. The Special Region of Yogyakarta (DIY) is a priority area for stunting intervention. Stunting is a chronic condition that describes stunted growth due to long-term malnutrition. Stunting is associated with an increased risk of illness and death and stunted mental and motor growth. Delayed motor development results in children not being able to perform developmental tasks appropriate to their age group. The purpose of this study was to determine the description of the application of the Health Belive Model to stunting toddlers in the Minggir Community Health Center. This research method using analytic survey using cross sectional approach. The variables of this research are perceived susceptibility, perceived severity, perceived benefits, perceived barriers, coes to action, self efficacy. The sample of this research is mothers who have babies and stunting toddlers. The results of the analysis show that there is a significant relationship. Statistically obtained the results of perceived vulnerability (OR: 1.21; 95% CI: 0.06-1.62; p <0.01), perceived severity (OR: 1.22; 95% CI: 0.08-1 , 67; p <0.01), and other independent variables do not have a significant relationship, namely the variable perception of prevention, self-efficacy, and Cues to Action. Together, all the independent variables in this logistic regression model are able to explain or predict the incidence of stunting in children under five. This research is expected to reduce stunting rates and empower mothers to pay more attention to the development of their toddlers and to prevent malnutrition in children under five.